2015
DOI: 10.1002/admi.201500239
|View full text |Cite
|
Sign up to set email alerts
|

Elaborately Designed Hierarchical Heterostructures Consisting of Carbon‐Coated TiO2(B) Nanosheets Decorated with Fe3O4 Nanoparticles for Remarkable Synergy in High‐Rate Lithium Storage

Abstract: and transition metal oxides (TMOs) [13][14][15][16] have recently been explored as promising anode candidates.TiO 2 , among other TMOs, is particularly attractive owing to its fascinating features including high structural stability, long cycle life, low cost, and high safety. [17][18][19][20][21] TiO 2 (B), as an unusual polymorph (bronze-phase) of TiO 2 , is found to have an open-channel structure and display a pseudo-capacitive behavior, thus enabling easier Li + diffusion and faster chargingdischarging cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 83 publications
(107 reference statements)
1
23
0
Order By: Relevance
“…Combining such nanostrucrtured materials with carbon‐based systems is also an attractive strategy to improve the diffusion capability of Li + /e − in TiO 2 . For instance, Jiang et al combined anatase/TiO 2 ‐B with conductive carbon and reduced graphene oxide (rGO), to form a hierarchically porous carbon‐coated mixed‐phase TiO 2 nanosheet/rGO composite (TiO 2 @C/rGO) through a one‐pot solvothermal process .…”
Section: Recent Developments In Hierarchy Design In Hmo Anodesmentioning
confidence: 99%
“…Combining such nanostrucrtured materials with carbon‐based systems is also an attractive strategy to improve the diffusion capability of Li + /e − in TiO 2 . For instance, Jiang et al combined anatase/TiO 2 ‐B with conductive carbon and reduced graphene oxide (rGO), to form a hierarchically porous carbon‐coated mixed‐phase TiO 2 nanosheet/rGO composite (TiO 2 @C/rGO) through a one‐pot solvothermal process .…”
Section: Recent Developments In Hierarchy Design In Hmo Anodesmentioning
confidence: 99%
“…It is well known that the crystallinity of nanostructured transition metal oxides can be further improved through heat treatment, which usually results in optimized electrochemical performance . To screen the proper conditions, neat V 2 O 5 nanowires were subjected to heat treatment at different temperatures (200, 300, and 400 °C).…”
Section: Figurementioning
confidence: 91%
“…Previously we have successfully assembled small entities (i.e. symmetric and asymmetric nanoparticles) on various two-dimensional matrices, including graphene, [37] transition metal dichalcogenides, [38,39] transition metal oxides, [40,41] and hexagonal BN. [42] Interestingly,i nt his work we found that larger entities such as V 2 O 5 nanowires can also be assembled on the Ndopedg raphene nanosheets in ad ense and uniform way,a s showni nF igure 2a and b.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure e presents the C 1s spectrum, in which the intense peak at 284.8 eV belongs to the C−C bonds originating from the carbonization of polydopamine. The tiny peak at 286.5 eV refers to the C−O bonds, which is consistent with the O 1s spectrum.…”
Section: Figurementioning
confidence: 99%